Perancangan Aplikasi E-Booking Service Sepeda Motor Honda Untuk Meningkatkan Kualitas Customer Relationship Management - Pangestu, Anjas Arya; Dalimunthe, Yulia Agustina (Universitas Labuhanbatu, 2023)
Medan is engaged in the service sector, namely servicing Honda motorcyclesThe service motorcyeles. Currently the service booking process is still manual and requires the eustomer lo come directly to the dealer, This information system will makeit easier for eustomers to hook their motorbike services online from their cellphones and also with this information system the customer can choosethe right time to do the service without having to come lo the motorcycle dealer first. This information system can also make it easier for customers to get information and interesting offers about Honda motorcycle services. This informnation system is built on a Web-based basis.